Babies can't eat kimchee! - Patz, Nancy (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
A baby sister must wait to grow up before doing big sister things, such as ballet dancing and eating spicy Korean food.